Dependence of phase transitions on halide ratio in inorganic CsPb(BrxI1−x)3 perovskite thin films obtained from high-throughput experimentation. Issue 43 (29th October 2020) - Näsström, H.; Becker, P.; Márquez, J. A.; Shargaieva, O.; Mainz, R.; Unger, E.; Unold, T.
Abstract : The heating and cooling phase diagram of CsPb(Br x I1− x )3 is determined by combinatorial synthesis and high throughput X-ray characterization. Abstract : In this communication, we present the phase diagram of CsPb(Br x I1− x )3 (0 ≤ x ≤ 1, 300–585 K) obtained by high-throughput in situ GIWAXS measurements of a combinatorial thin film library. We find that all compositions convert to the cubic perovskite phase at high temperature and that the presence of bromide in the films stabilizes the metastable perovskite phases upon cool down. In accordance with recent predictions from DFT-calculations, the transition temperatures monotonically decrease with increasing bromide content.